Influence of Authoritarian Parenting Style on the Self-Esteem and Self-Efficacy of Psychology Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Since there is a gap in research regarding the potential negative consequences of differentparenting styles, it is essential to focus on the study and comprehension of authoritarianparenting. This involves examining how this particular parenting style can affect a child'ssense of self-esteem and self-efficacy and identifying ways to reduce or prevent thesenegative effects.The researchers utilized a 4-point Likert scale to measure the respondents’ levels of self-esteem and self-efficacy and also aimed to assess the level of authoritarian parenting amongparents. The results showed a moderate level of authoritarian parenting among parents.Results showed that there was a significant relationship between authoritarian parenting andthe respondents' self-esteem and self-efficacy. The study utilized the Pearson CorrelationCoefficient to establish this relationship between the two variables. As the computed value of rwas higher than the critical value, the null hypothesis was rejected. Therefore, the studyconcludes that there is a significant correlation between the influence of authoritarianparenting and the self-esteem and self-efficacy of the students.The researchers gathered data and analyzed it to produce a summary of the findings. Thissummary included key information and insights that were derived from the data. Using thisinformation, the researchers formulated conclusions that helped to interpret and make senseof the findings. Subsequently, based on their conclusions, the researchers developedrecommendations that aimed to address any issues or challenges identified in the study.
Keywords: Psychology